Selective Empathy in the Re-designed Imperial War Museum London: Heroes and Perpetrators - Koureas, Gabriel (My University, 2018)
Koureas concentrates on curatorial practices in the Imperial War Museum to discuss the complexities of the representation of the perpetrator. Focussing on particular exhibits and unseen narratives from the archives of the museum, the chapter argues that a hierarchy of empathic identification is in operation. This hierarchy ranks certain conflicts, often in the name of security and humanity, as justifiable, and labels particular populations as ‘heroic’ and to be empathised with, whilst others are reduced to perpetrating and violent ‘insurgents.’ These practices result in the normalisation of certain acts of violence and the condemnation of others. Koureas addresses the dynamics and exchanges that take place between memory, history (and in particular, British Colonial Wars), the victim and perpetrator, and selective empathy in order to reveal the contingent and ambivalent nature of ‘heroes’ and ‘perpetrators’ and their representations.
Keywords: Colonial Wars; Unseen Narrator; Empathic Identification; Ambivalent Nature; British Cultural Memory